2021
DOI: 10.1038/s41388-021-01720-w
|View full text |Cite
|
Sign up to set email alerts
|

Liver x receptor alpha drives chemoresistance in response to side-chain hydroxycholesterols in triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) is challenging to treat successfully because targeted therapies do not exist. Instead, systemic therapy is typically restricted to cytotoxic chemotherapy, which fails more often in patients with elevated circulating cholesterol. Liver x receptors are ligand-dependent transcription factors that are homeostatic regulators of cholesterol, and are linked to regulation of broad-affinity xenobiotic transporter activity in non-tumor tissues. We show that LXR ligands confer chemoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…To confirm if the protein bands were LXRa variants, we first performed siLXRa treatments in cell lines. Using previously validated (Hutchinson et al, 2021) siRNA duplexes (Origene trisilencers) against LXRa and LXRb, we found that the protein bands predicted by size to be a1, a2, a3, a5, and b1 were all significantly reduced by targeted siRNA in all cell lines tested (all p < 0.05; Figure S10). Note that a4 and b4 were not expressed in cell lines and so could not be validated in this way.…”
Section: Validation Of Isoform Identity Bands Representing Lxr Variants Were Reduced By Targeted Sirnamentioning
confidence: 86%
See 2 more Smart Citations
“…To confirm if the protein bands were LXRa variants, we first performed siLXRa treatments in cell lines. Using previously validated (Hutchinson et al, 2021) siRNA duplexes (Origene trisilencers) against LXRa and LXRb, we found that the protein bands predicted by size to be a1, a2, a3, a5, and b1 were all significantly reduced by targeted siRNA in all cell lines tested (all p < 0.05; Figure S10). Note that a4 and b4 were not expressed in cell lines and so could not be validated in this way.…”
Section: Validation Of Isoform Identity Bands Representing Lxr Variants Were Reduced By Targeted Sirnamentioning
confidence: 86%
“…We previously reported that LXRa expression is positively correlated to target gene expression in ER-negative patients who had relapsed and/or died due to their disease (Event patients) but not those who survive (Hutchinson et al, 2021). Here, we tested the hypothesis that differential LXR splice variant expression between cancers may contribute to disease etiology via their ability to control expression of gene targets.…”
Section: Lxr Splice Variants Are Differentially Correlated With Expression Of Target Genes In Event and No Event Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, activation of LXR by LXR agonist inhibited breast cancer cell proliferation in vitro [51]. Interestingly, Hutchinson et al reported that activation of LXR by LXR antagonist contributes to resistance of triple negative breast cancer to epirubicin in vivo [52]. Possibly, the efficacy of specific agents depends on in vitro vs. in vivo methods, tumor type or genotype, or the specific regimen or drug combination evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Leeds teaching Hospitals NHS Trust, Leeds, UK Detoxification and nutrient metabolism are connected in healthy tissues to prevent toxic accumulation of metabolic intermediates and end-products (1) . These pathways also enhance processing of xenobiotics such as anti-cancer drugs (2) . Resistance to anti-cancer drugs remains a major barrier to successful treatment of many cancer types, yet clinical tools that predict which treatment regimen would be most effective at individual patient level remain underdeveloped.…”
mentioning
confidence: 99%